Religion as an Ethical Pillar in Asset Management and Public Services in the Digital Era in Sumedang Regency - Febianti, Fepi (FISIP UIN Sunan Gunung Djati Bandung, 2025)
Research Problem: Pervasive gaps in ethical governance undermine asset management and digital public service delivery at the local level. In Sumedang Regency, the extent to which religious values can function as an ethical pillar to strengthen accountability, transparency, and public trust remains underexamined. Research Purposes: (1) To analyze how religious ethics inform the governance of regional assets and digital public services in Sumedang Regency; (2) to assess their contribution to accountability, transparency, and community trust; and (3) to identify practical pathways for embedding religious values into local government operations. Research Methods: A qualitative descriptive design combining document/policy review, semi-structured interviews with relevant stakeholders, and analysis of secondary data. Data were thematically coded to trace linkages between explicit religious values (e.g., honesty, responsibility, fairness) and observed governance practices and outcomes. Results and Discussion: Findings indicate that the explicit integration of religious values functions as a moral baseline for decision-making in asset registration, utilization, and oversight, and for the design and delivery of digital public services. Reported effects include clearer audit trails, more consistent rule adherence, and improved responsiveness in service workflows—factors associated with higher perceived accountability and transparency. However, impacts are uneven and contingent on leadership commitment, codification in SOPs, staff capacity, and the alignment of digital systems with ethical safeguards (e.g., auditability and privacy). Research Implications and Contributions: Policy-wise, the study recommends formalizing value-based codes of conduct within asset and service SOPs, embedding ethics checks in SPBE/digital platforms (e.g., audit trails, disclosure dashboards), and institutionalizing training and public feedback loops. Practically, it offers a context-sensitive framework for operationalizing religious values in local e-governance. Academically, it contributes to the literature on ethical digital governance by demonstrating how religiosity—conceptualized as actionable virtues—can complement modern technological controls to enhance public trust and the effective use of public assets.